Aspidistra albovillosa (Asparagaceae), a new species from Guangxi, China - Ding, Tao; Pan, Bo; Lin, Chun-Rui (Phytotaxa, 2023)
Aspidistra albovillosa, a new species of Asparagaceae from Guangxi, southern China, is described and illustrated. The new species is similar to A. ovatifolia, but differs by the appendages at the base of the perianth lobes are purplish red, sometimes white and slightly rolled upwards at apex, tube adaxially with white villous densely, stigma upper surface yellowish white, slightly undulate and 6 (or 8) lobed at margin. The new species is currently known only from the Karst areas in central Guangxi. Colour plates of the two similar species and line drawing are provided for comparison.